2020
DOI: 10.1177/0361198120957003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Freeway Exit Ramp Terminal Design Practices to Deter Wrong-Way Driving in Different States

Abstract: Although wrong-way driving (WWD) crashes are rare compared with other crashes, the severe outcomes resulting from these crashes make them an important traffic safety issue, especially on freeways. The initial point of origin for the majority of WWD crashes is the exit ramp terminal. During 2009–2013, the exit ramp terminals of full diamond and partial cloverleaf interchanges in Alabama experienced considerably higher frequency of wrong-way entries compared with those in Illinois. In this study, a comparative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The remaining detections included 61 (8.4%) that likely turned around (as only the incoming camera was activated) and 92 (12.7%) that activated multiple cameras but were not confirmed to have either turned around or entered the mainline. Most of the WWD detections occurred during nighttime (482 or 66.4%), which agrees with previous research on WWD crashes ( 3 11 ).…”
Section: Analysis Of Wrong-way Driver Behaviorsupporting
confidence: 92%
See 2 more Smart Citations
“…The remaining detections included 61 (8.4%) that likely turned around (as only the incoming camera was activated) and 92 (12.7%) that activated multiple cameras but were not confirmed to have either turned around or entered the mainline. Most of the WWD detections occurred during nighttime (482 or 66.4%), which agrees with previous research on WWD crashes ( 3 11 ).…”
Section: Analysis Of Wrong-way Driver Behaviorsupporting
confidence: 92%
“…A significant amount of research has been done on limited access WWD crashes throughout the U.S. WWD crashes in Alabama, Arizona, Florida, Illinois, Kansas, Louisiana, North Carolina, Tennessee, and Texas have been analyzed to identify significant factors and characteristics, with common characteristics being driver intoxication, older drivers, and nighttime conditions (3)(4)(5)(6)(7)(8)(9)(10)(11). The effects of exit ramp terminal design on WWD crashes at full diamond and partial cloverleaf interchanges have also been studied, with results showing that having non-traversable medians on the crossing road, reducing the exit ramp throat width, and having a wide median between adjacent exit and entrance ramps could reduce WWD crashes (11).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that crash frequency increased on ramp segments with higher AADT, short ramp lengths, or both. Atiquzzaman and Zhou conducted a comparative analysis of wrong-way driving (WWD) crashes that occurred at exit ramp terminals in Illinois and Alabama ( 18 ). The crash data were collected at ramp terminals of full diamond and partial cloverleaf interchanges in these two states for the years 2009 to 2013.…”
Section: Literature Reviewmentioning
confidence: 99%